ANALYSIS OF PERFORMANCE AND REVENUE OF LAYING HENS BUSINESS ADD THE SUPPLEMENTS IN DRINK WATER (Case Study in Candikusuma Village, Melaya District) - A. I K., Sudiana; Sukanata, I W.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2020)
This study purpose to determine the performance analysis and business income of laying hens that are suplemantated through drinking water. This research was conducted at a laying chicken farm owned by Ni Made Dewi Maharatih in Candikusuma Village, Kecamatan Melaya, Jembrana Regency, Bali Province which was conducted for 4 months, from preparation to data analysis. This study used a completely randomized design (CRD) with 3 treatments and 5 replications. The variables observed in this study were egg production, Hen Day Production, egg grade, income, R/C ratio and break even point. The results showed that egg production and Hen Day Production in laying hens that were given supplementation through drinking water with a dose of 0.05% and 0.1% statistically showed significantly different results (P> 0.05) when compared with control ( drinking water without supplementation). The results of the analysis of production performance aimed to increase egg production by adding supplements to drinking water by 0.05% and 0.1% by 3.3% and 9.1%. The results of income analysis showed the addition of supplements to drinking water as much as 0.1% showed the best results with a net income of Rp 314,743.06 / month, R / C ratio of 1.28, BEP units of 367 items, BEP price of Rp 1,003 / item and sales BEP of IDR 483,000. Based on the results of the study it can be concluded that the addition of supplementation through drinking water can improve production performance and business income of laying hens. The Keywords: Supplements, performance, laying hens, income.